APLICACIÓN DE UN SISTEMA DE COSTOS POR PROCESOS EN LA PANADERÍA AYNARA DE LA CIUDAD DE LOJA, PERIODO JULIO-SEPTIEMBRE 2018” - Acevedo Rengel, Jefferson David (2020)
The “APPLICATION OF A SYSTEM OF COSTS BY PROCESSES IN THE AYNARA BAKERY OF THE CITY OF LOJA, JULY-SEPTEMBER 2018 PERIOD”, was carried out in order to determine the cost of production obtained in the bakery, this information will be vital importance to improve the efficiency of economic activity such as sales, purchases, costs, expenses, inventories and other movements that are made within the company, which will help the owner to obtain good results, optimize their production and obtain a better profitability , so that you can achieve better administration. As a first objective, the collection of all the information necessary to carry out an initial inventory was proposed, which the bakery has and in turn the source documents to be able to carry out the accounting process during the established period, for the second objective all the documents were designed , records and accounting assistants that will be required for the control of each of the cost elements such as raw material, labor and indirect manufacturing costs, in which each movement made was recorded. For the application of the Process Cost System, it was necessary to identify each of the stages of bread making, thus obtaining the following processes: 1) Dosing and weighing of the Raw Material; 2) Mixed, Kneaded and Division of the Mace; 3) Formed; 4) Fermentation; 5) Baking 5 Bread; This facilitated the determination of the unit cost of bread at $ 0.0959 and with a total production cost of $ 17,268.36, in the period July-September 2018. Once these values were obtained, the accounting process began, concluding with the presentation of the financial statements that will allow the correct decision making. Among the most relevant results when studying the elements of the system of costs by processes, it was possible to identify that the company does not have all the supporting documents, does not apply policies, procedures, records and accounting assistants that allow maximum efficiency of resources. The application of a system of costs by processes will allow to improve the business management, since it will help the administration to carry out corrective actions to achieve certain objectives such as cost reduction, increase in income, product quality and maximization of Profits. .